Misuse of public office for organizational gain?: Brazilian political parties in corruption scandals - Trombini, Maria Eugenia (Political corruption and organizational crime, 2021)
In Brazil’s democratic history, two corruption scandals have exposed political parties and politicians to the public opinion and law-enforcement like no others. The first, Mensalão, roughly meaning “big monthly stipend” was coined to describe clandestine payments made by the Workers’ Party (PT) to congressional allies in return of support for its legislative agenda and occurred during the first term of president Luiz Inácio Lula da Silva’s presidency. The second, Petrolão, alluding to Brazil’s state-controlled oil giant, Petrobras, started in 2014 and unveiled a web of illegal payments connecting public contractors, civil servants and politicians channeling money from deals into secret slush funds.
Gesehen am 17.12.2021